Wanted: A systematic review of the most trafficked songbirds in a Neotropical hotspot - Ferrari, Giuliana C. P.; Rheingantz, Marcelo Lopes; Rajão, Henrique; Lorini, Maria Lucia (Frontiers in Forests and Global Change, 2023)
The illegal wildlife trade is one of the main factors of biodiversity loss worldwide. Brazil, the largest country in South America, is a hub of wildlife trafficking, but availability of information on the issue is constrained to specific regions and to Portuguese speakers. Knowledge gaps hinder the establishment of targeted countermeasures in the fight against the illegal wildlife trade. Thousands of animals are seized from IWT and sent to wildlife centers each year. Here, we reviewed the literature on seized songbirds for the Brazilian Atlantic Forest, a global hotspot of biodiversity. Using a systematic review approach, we compiled a database with all available papers containing seizure records for the Brazilian Atlantic Forest. We focused on the 10 most seized species in each study to construct a comprehensive view of the main victims of the illegal trade. We reported 23 studies in 20 locations throughout the BAF. In 19 years, 139,000 passerines were recorded, distributed in 47 species – and two genera – across 10 families. Thraupidae was the most important family, with 27 species in the list and comprising 70% of individuals recorded. We highlighted the preference for granivorous birds and birds deemed good singers. There were few threatened species in the top list, but many of the ones included have population trends of decline, indicating a conservation issue that can direly affect even currently common species if the high demand continues. We appointed knowledge gaps within the Brazilian scenario of wildlife trafficking and provided practical recommendations on the issue considering the global scenario of IWT.